2014
DOI: 10.1186/s12879-014-0583-3
|View full text |Cite
|
Sign up to set email alerts
|

Profiling bacterial community in upper respiratory tracts

Abstract: BackgroundInfection by pathogenic viruses results in rapid epithelial damage and significantly impacts on the condition of the upper respiratory tract, thus the effects of viral infection may induce changes in microbiota. Thus, we aimed to define the healthy microbiota and the viral pathogen-affected microbiota in the upper respiratory tract. In addition, any association between the type of viral agent and the resultant microbiota profile was assessed.MethodsWe analyzed the upper respiratory tract bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 55 publications
8
65
1
Order By: Relevance
“…As reported before from adult studies, we found a lower diversity and a higher density during symptomatic HRV colonization (20,25,26). The rather high intra-and interindividual heterogeneity is also in line with previous data (10,25) and supports the hypothesis of a different composition of the microbiota during viral infection (27), possibly explained by an outgrowth of potential pathogens triggered through HRV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As reported before from adult studies, we found a lower diversity and a higher density during symptomatic HRV colonization (20,25,26). The rather high intra-and interindividual heterogeneity is also in line with previous data (10,25) and supports the hypothesis of a different composition of the microbiota during viral infection (27), possibly explained by an outgrowth of potential pathogens triggered through HRV.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in adults reported no sustained changes in healthy subjects (20), whereas in chronic obstructive pulmonary disease (COPD) patients, a higher abundance of Haemophilus influenzae and an increase in 16S rRNA gene copy number could be seen up to 42 days after infection (20). Our finding of a higher abundance of Moraxellaceae and a lower abundance of Staphylococcaceae after HRV infection was not reported before, but other studies described an association of a higher abundance of Moraxellaceae with acute respiratory infections (ARIs) (23) and viral colonization (26). These results support the hypothesis of persistent bacterial outgrowth after viral infection, especially as Moraxella catarrhalis is a potential pathogen in respiratory disease (1).…”
Section: Discussionsupporting
confidence: 45%
“…The relative abundances of these OTUs were significantly correlated with one another (Figure 4A); we hypothesise this is related to the protection provided by the Moraxella biofilm (Tan et al, 2007), which can release outer membrane surface proteins that protect other bacteria from complement-dependent killing. Other groups have previously reported reduced upper airway microbial diversity during or prior to ARIs (Frank et al, 2010;Santee et al, 2016;Yi et al, 2014); our data supports this, both in terms of enrichment of a small number of community profiles (MPGs) during ARI, and a higher abundance of ARI-associated OTUs and lower alpha diversity within these MPGs compared to that observed in the absence of ARI symptoms (Figures 2B, S3; Tables S1, S3). We therefore propose that overgrowth of these particular taxa may tip the balance towards respiratory symptomatology, either by direct action as invasive pathogens or via indirect dysregulation of the local immunological milieu.…”
Section: Discussionsupporting
confidence: 89%
“…This observation contrasts with previous metagenomic-based studies of vertebrates (mostly humans) showing a lower microbial diversity and/or richness among the patient group versus the control group for certain respiratory pathologies for instance. 40,41 This could be related to the carriage of some bacterial genera such as Burkholderia, which was well represented in Pf-free specimens of both species. Moreover, patients often present an increasing proportion of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 98%